SUPPORT PROGRAMMES FOR THE DEVELOPMENT OF RURAL ENTREPRENEURSHIP IN POLAND - Chmieliński, Paweł (Economics of Agriculture, 2009)
The evolution of rural entrepreneurship is intrinsic to multifunctional rural development. Entrepreneurship is not just a part of economic development – it is the basis of long-term economic development. Accession to the EU brought new opportunities for rural entrepreneurship and financial sources: start-up and investment capital. The study is aimed at outlining the framework of analysis for policy aspects of entrepreneurship development in Poland after accession to the European Union. Analyse shows positive influence of EU co-financed measures on entrepreneurship development in Poland however it is still the state main role to promote development of non-agricultural activities on rural areas is not only support through EU-programmes but also by implementing favourable tax policy as well as improvement of the legislation quality.